Procedural simplification of left atrial appendage occlusion using the VersaCross connect system: First in‐human experience. Issue 1 (22nd November 2022) - Perrin, Nils; McAlister, Cameron; Tsang, Michael; Mondésert, Blandine; Ibrahim, Réda; Saw, Jacqueline
Abstract: Background: Left atrial appendage occlusion (LAAO) has emerged over the last two decades as an efficient and safe alternative to oral anticoagulation for stroke prevention. However, LAAO remains challenging due to the variety of anatomies and the multiple steps required to complete the procedure. Aims: We report the first series of in‐human experience of the new all‐in‐one VersaCross Connect system designed to access the left atrium in conjunction with the delivery sheath for deployment of the WATCHMAN FLX device. Methods: We prospectively included the first nine consecutive cases of LAAO using the new VersaCross Connect system for WATCHMAN FLX device implantation at the Montreal Heart Institute and Vancouver General Hospital and collected procedural duration (defined as time from femoral access to closure) and time from transseptal puncture to device delivery. Results: VersaCross Connect system use for WATCHMAN FLX implantation was successful in all patients. No procedural complication was reported. Mean procedural time was 31 ± 6.3 min with a fluoroscopy time of 6.7 ± 4.9 min. The mean delay between the transseptal puncture and device implantation was 12.2 ± 1.9 min. Conclusions: We showed that the VersaCross Connect system was safe and successfully used in all first nine cases. This new system helped improve the efficiency of the procedure.